Agress??o constitucional na exig??ncia de garantia pr??via como condi????o de admissibilidade dos embargos ?? execu????o fiscal - Moreira, M??rcio Gon??alves (2015)
In a Lawful Democratic State the law should be in line with the Federal Constitution, as even the legislature owes allegiance to it. Possible legal instrument that affronts to the Constitution must be removed from the legal system. The infra-constitutional legislation should only be applied if it passes through the filter of the Constitution. The Judicial Law Review can only have a normative instrument object edited under the aegis of the Constitution parameter to control. So for pre-constitutional rules are the theories of reception and revocation, which are used to solve the problem of the law that deals with the judgment assurance requirement to oppose a legal resource for tax foreclosure, since Law No. 6830 / 80 was issued under the aegis of the Federal Constitution repealed by the present Constitutional Book. The new constitutional order as a fundamental right guaranteed broad access to justice, that is, unrestricted, so to require the deposit of certain amount of money to discuss tax enforcement is manifestly against the Constitution because it constitutes obstacle to free access to the judiciary. Including even at the administrative level does not admit anymore the deposit as a condition of admissibility of appeals.